A graphene-based compatible flexible film with ultra-wideband microwave absorption and low infrared emissivity. (November 2022) - Huang, Qianqian; Wang, Zhide; Zhao, Yue; Wu, Yue; Tang, Shaolong; Ji, Guangbin
Abstract: Excessive electromagnetic radiation affected equipment and human health. Therefore, it is urgent to eliminate hazardous electromagnetic waves. In this work, a green synthesis technology was adopted to obtain a novel protective composite. Combining CuS/ZnS (CZS) and graphene oxide (GO), the prepared composites can absorb more than 99% electromagnetic waves. CZS nanoparticles are evenly distributed on the surface and inside of reduced graphene oxide that can form abundant interfacial polarization to enhance electromagnetic attenuation ability. The composite film has an extensive effective absorption bandwidth ( f e ), up to 10.14 GHz under the filling ratio of 12%, covering the X-band and Ku-band. More importantly, the absorption bandwidth could reach 6.38 GHz with the ultra-low filling rate is 6%. In addition, the composite film also has a relatively low infrared emissivity of 0.577, which can meet the requirements of low infrared radiation. These results are of great significance for designing and synthesizing high-performance materials for microwave infrared compatible pollution protection. Graphical abstract: In this work, the graphene oxide and sodium alginate were used as substrates, and the novel flexible composite films were obtained by compounding them with CuS/ZnS particles. The prepared absorbent can absorb more than 99% electromagnetic waves in the environment for efficient electromagnetic pollution protection. Image 1 Highlights: The film can absorb more than 99% of electromagnetic waves. The composite film could reach 10.14 GHz at the ultra-low filling ratio. The significant reduction of radar cross section under the condition of real far field is 26.3 dB m 2 .